Ursolic acid alleviates hypercholesterolemia and modulates the gut microbiota in hamsters. Issue 7 (22nd June 2020) - Hao, Wangjun; Kwek, Erika; He, Zouyan; Zhu, Hanyue; Liu, Jianhui; Zhao, Yimin; Ma, Ka Ying; He, Wen-Sen; Chen, Zhen-Yu
Abstract : Ursolic acid exhibited the cholesterol-lowering activity via suppressing the cholesterol absorption and altering the gut microbiota. Abstract : Ursolic acid (UA) is a triterpenoid acid widely abundant in fruits and vegetables such as apple, blueberry and cranberry. The present study was carried out to investigate the effect of UA supplementation in diet on blood cholesterol, intestinal cholesterol absorption and gut microbiota in hypercholesterolemic hamsters. A total of thirty-two hamsters were randomly assigned to four groups and given a non-cholesterol diet (NCD), a high-cholesterol diet containing 0.1% cholesterol (HCD), an HCD diet containing 0.2% UA (UAL), or an HCD diet containing 0.4% UA (UAH) for 6 weeks. Results showed that UA supplementation reduced plasma cholesterol by 15–16% and inhibited intestinal cholesterol absorption by 2.6–9.2%. The in vitro micellar cholesterol solubility experiment clearly demonstrated that UA could displace 40% cholesterol from micelles. In addition, UA decreased the ratio of Firmicutes to Bacteroidetes, whereas it enhanced the growth of short chain fatty acid (SCFA)-producing bacteria in the intestine. In conclusion, UA possessed a cholesterol-lowering activity and could favorably modulate the gut microbiota.